Technological lessons from the Fukushima Dai-Ichi Accident - Dion-Schwarz, Cynthia (Research report (Rand Corporation), 2016)
"Following the devastating Tohoku earthquake and tsunami that afflicted Japan in March 2011, some of the reactors of the Fukushima Dai-Ichi nuclear power plant began to release radioactive material into the environment. This study draws lessons from this experience regarding technological countermeasures to radioactive contamination to improve responses to future radiological or nuclear contingencies. Specifically, it focuses on how technologies were used to measure contamination over space and time, to limit the dispersal of radioactive material in the environment, to decontaminate areas or items, and to store radioactive materials for extended periods. The authors gathered data by conducting extensive literature reviews and dozens of interviews with experts in both Japan and the United States. The report analyzes how technologies were used successfully and identifies capability gaps that could be redressed through novel technologies or improved use of existing technologies. Also included is an abbreviated bibliography for further reading"--Publisher's description.